If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4 + -1x) + -3(2x + -4) = 0 (4 * 2 + -1x * 2) + -3(2x + -4) = 0 (8 + -2x) + -3(2x + -4) = 0 Reorder the terms: 8 + -2x + -3(-4 + 2x) = 0 8 + -2x + (-4 * -3 + 2x * -3) = 0 8 + -2x + (12 + -6x) = 0 Reorder the terms: 8 + 12 + -2x + -6x = 0 Combine like terms: 8 + 12 = 20 20 + -2x + -6x = 0 Combine like terms: -2x + -6x = -8x 20 + -8x = 0 Solving 20 + -8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + -8x = 0 + -20 Combine like terms: 20 + -20 = 0 0 + -8x = 0 + -20 -8x = 0 + -20 Combine like terms: 0 + -20 = -20 -8x = -20 Divide each side by '-8'. x = 2.5 Simplifying x = 2.5
| 3/7+N=4/3 | | 8y-9=9 | | x-(4(3.5)-7)=5(3.5)-(3.5+21) | | 4(7y)= | | 2x+3x-x=4 | | -81/2=-15r | | 15(3x+5)=120 | | y=10x+56 | | 8.2x-2.3=94.4 | | 7/9+x11/9 | | 29+8r=3(4r-1) | | 2x+4y=31/2 | | 6(2x-1)+1=12x-5 | | 25-b=37 | | 6x+7(x+3)=86 | | 37=10+x | | 14-(6-(3*r))=(4*r)-r | | 100-5n= | | -14+5t=3t | | 5/6y+1/5(y-6)=(y+1)/6 | | 3/7+N=11/3 | | 2(4x-2)=10x-12 | | 1/5*7/1 | | 10x+2=5x-9 | | 124=64/x | | 4*-0.5= | | x+4/30=13/15 | | 2/5x15/18 | | 6b+10-2b=-4b | | 8t^2-64t+281=0 | | 2x+21/3=5 | | 8n-(2n-3)= |